Cortisol Impacted on Explicit Learning Encoding, but Not on Storage and Retrieval, and Was Not Associated With Sleep Patterns—Results From the Trier Social Stress Test for Children (TSST-C) Among 9-Years Old Children - Brand, Serge; Mikoteit, Thorsten; Kalak, Nadeem; Sadeghi Bahmani, Dena; Lemola, Sakari; Gerber, Markus; Ludyga, Sebastian; Bossard, Madleina; Pühse, Uwe; Holsboer-Trachsler, Edith; Hatzinger, Martin (Frontiers in Psychology, 2018)
Background: Learning is the relatively permanent change of behavior as a result of experience and tightly related to memory and cognition. Learning is particularly important for children. Further, restoring sleep is associated both with improved learning performance and lower cortisol levels as a proxy of the so-called hypothalamus-pituitary-adrenocortical axis activity (HPA-AA). With the present study, we investigated, if and to what extent explicit learning performance was associated with cortisol levels at baseline and under challenge conditions and with objective sleep dimensions among 9-years old children. Methods: A total of 39 children (mean age = 9.5 years; 39% females) took part in the study. Verbal and figural working and long-term memory were tested before and after the Trier Social Stress Test for Children (TSST-C). Further, children underwent sleep-EEG assessment, and cortisol awakening response (CAR) was assessed. Results: Higher cortisol levels were associated with lower explicit learning encoding (verbal, but not figural learning). Higher verbal and figural working and long-term memory performance predicted lower cortisol secretion under the TSST-C, along with higher verbal and figural working and long-term memory performance after the TSST-C. Cognitive test performances were not mediated by cortisol secretion under the TSST-C. Cognitive performance, cortisol secretion under challenge (TSST-C) and basal conditions (morning) and sleep patterns were unrelated. Conclusions: The pattern of results suggests that among a sample of 9-years old children cortisol secretion and stages of memory processes (encoding, storage, retrieval) are associated in a complex and bi-directional way. Further, it appears that cognitive-emotional processes underlying cognitive performance and its evaluation might impact on subsequent cortisol secretion as a proxy of neuroendocrinological response to cognitive-emotional processes. Last, cognitive performance and cortisol secretion under challenge conditions were not related to objective sleep patterns and baseline cortisol secretion.